Innate Cells: The Alternative Source of IL-17 in Axial and Peripheral Spondyloarthritis? - Rosine, Nicolas; Miceli-Richard, Corinne (Frontiers in Immunology, 2021)
Spondyloarthritis (SpA) is a chronic inflammatory rheumatism characterized by inflammation of sacroiliac joints, peripheral joints, and spine. The Assessment of SpondyloArthritis Society describes three disease forms: axial (axSpA), peripheral, and enthesitic SpA. Each may be associated with extra-articular manifestations: psoriasis, inflammatory bowel disease, and acute anterior uveitis. Genome-wide association studies performed in axSpA and psoriatic arthritis (PsA) have shown a shared genetic background, especially the interleukin 23 (IL-23)/IL-17 pathway, which suggests pathophysiological similarities. The convincing positive results of clinical trials assessing the effect of secukinumab and ixekizumab (anti-IL-17A monoclonal antibodies) in axSpA and PsA have reinforced the speculated crucial role of IL-17 in SpA. Nevertheless, and obviously unexpectedly, the differential efficacy of anti-IL-23–targeted treatments between axSpA (failure) and PsA (success) has profoundly disrupted our presumed knowledge of disease pathogeny. The cells able to secrete IL-17, their dependence on IL-23, and their respective role according to the clinical form of the disease is at the heart of the current debate to potentially explain these observed differences in efficacy of IL-23/IL-17–targeted therapy. In fact, IL-17 secretion is usually mainly related to T helper 17 lymphocytes. Nevertheless, several innate immune cells express IL-23 receptor and can produce IL-17. To what extent these alternative cell populations can produce IL-17 independent of IL-23 and their respective involvement in axSpA and PsA are the crucial scientific questions in SpA. From this viewpoint, this is a nice example of a reverse path from bedside to bench, in which the results of therapeutic trials allow for reflecting more in depth on the pathophysiology of a disease. Here we provide an overview of each innate immunity-producing IL-17 cell subset and their respective role in disease pathogeny at the current level of our knowledge.